2020
DOI: 10.1177/2165079920910758
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reporting of Type II Workplace Violence Among Home Health Care Nurses

Abstract: Background: Home health care nurses (HHNs) work alone in patients’ homes. They experience high rates of Type II (client/patient-on-worker) workplace violence (WPV); however, little is known about the extent and factors of their reporting. Methods: A convenience sample of employees aged 18 years and older and working as an HHN or management staff were recruited from a U.S. nonprofit home health care agency. To describe the extent of reporting of WPV events, an HHN survey was conducted. To identify the barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…One out of 10 (9.5%) RNs in this study expressed more difficulty in reporting the violent incident to management during the pandemic than before. Studies in various health care settings have shown that barriers of Type II WPV reporting include lack of time to report; belief that violence is part of the job; unstandardized reporting process; ambiguity on the reportability of violence, including an unclear definition of violence; and lack of management support (Byon et al, 2020; Pompeii et al, 2016; Sato et al, 2013). It is likely that some of these factors for underreporting may have been elevated during the pandemic and become more challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One out of 10 (9.5%) RNs in this study expressed more difficulty in reporting the violent incident to management during the pandemic than before. Studies in various health care settings have shown that barriers of Type II WPV reporting include lack of time to report; belief that violence is part of the job; unstandardized reporting process; ambiguity on the reportability of violence, including an unclear definition of violence; and lack of management support (Byon et al, 2020; Pompeii et al, 2016; Sato et al, 2013). It is likely that some of these factors for underreporting may have been elevated during the pandemic and become more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The harmful but pervasive belief that violence is part of nursing may have solidified during the pandemic, and the nurses might have felt that they had to provide compassionate health care to the sick, even to those whose behaviors were violent. And the nurses might have found it difficult to report violent behaviors, rationalizing such behaviors were possibly related to the frustration the pandemic had put on their patients, and they were obliged to tolerate and not report them (Byon et al, 2020). The pandemic also restrained the support and resources that management could utilize, thus adding challenges for nurses to report violent incidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor limiting the nurse's ability to report was confusion about whether an event should be considered aggressive. Nursing victims had different understandings about aggression terminology and which events qualified for reporting, contributing to their underreporting (Byon et al, 2020;Ferns & Chojnacka, 2005;Findorff, 2003;Mahoney, 1991;Martell, 2014;Natan et al, 2011;Rodriguez-Acosta, 2007;Song et al, 2021).…”
Section: Ability To Reportmentioning
confidence: 99%
“…[13][14][15] Reasons home care workers may not report violence include growing tolerance to violence, concerns of being blamed for the violence, losing working hours or their jobs, holding a temporary work visa, and unfamiliarity with legal system. 14,[16][17][18][19] Overall, it was not uncommon that home care workers were subject to different forms of violence perpetrated by clients.…”
mentioning
confidence: 99%